Embedding instruments & modules into an IEEE1451-FPGA-Based Weblab infrastructure - Costa, Ricardo J. (2014)
Adopting standard-based weblab infrastructures can be an added value for spreading their influence and acceptance in education. This paper suggests a solution based on the IEEE1451.0 Std. and FPGA technology for creating reconfigurable weblab infrastructures using Instruments and Modules (I&Ms) described through standard Hardware Description Language (HDL) files. It describes a methodology for creating and binding I&Ms into an IEEE1451-module embedded in a FPGA-based board able to be remotely controlled/accessed using IEEE1451-HTTP commands. At the end, an example of a step-motor controller module bond to that IEEE1451-module is described.